Refugee social work in Lebanon: does the faith of the social worker provide support?. Issue 3 (3rd July 2021) - Hagues, Rachel; Cecil, David; Ghanem, Aimee; Mansour, Rania; Robbins, David
ABSTRACT: Recognizing that faith plays a significant motivational and coping role for many working in stressful conditions, this study examines the effects of faith on social workers in Lebanon working with refugees (N = 47). Data were collected using a structured interview guide in individual interviews and focus groups. Participants also completed a brief ordinal instrument. While results do reveal that numerous social workers in Lebanon working with refugees rely on faith for coping and motivation, findings suggest significant variability both in terms of perceived stress levels and extent of reliance on faith. Findings indicate the importance of teamwork and faith in humanity. Motivation often came from a belief in the cause or the refugees they were serving, and from a sense that they were doing God's work. Implications for practice are discussed.